STRUCTURAL TRANSFORMATION OF NANO – MERCURY OXIDE UNDER HIGH PRESSURE - T., Jayaprakash (International Journal of Psychosocial Rehabilitation, 2017)
Nanostructured orthorhombic mercury oxide is prepared by sonochemical reaction.  The influence of pressure on the structural properties are investigated by Energy Dispersive X- ray Diffraction  upto 15 GPa.  For the increasing pressure no transition is observed.  The volume fraction decreases monotonically as the pressure increases.  It has been observed that the particle size reduction enhances the first order transition pressure and the stability of the phase has increased.